Socio-economic aspects of the intensive growing of the Cowpeas ( Vigna unguiculata (L.) Walp.) in Kano, northern Nigeria - Van Damme, Patrick; Sampers, Wim; Pauwels, Frans (Afrika Focus, 1986)
The costs and benefits of single crop cowpea and cowpea grown in, a traditional mixed cropping system are calculated for the Kano area, in northern Nigeria. If all the technical requirements are met, single crop cowpea is more profitable, on a financial return per unit land basis, than the traditional crop mixture. A one year effort to try and familiarize traditional farmers with a new variety and new production methods is clearly not enough and may even demotivate a number of farmers when the yields, and financial returns, are low. To ensure that the improved technologies are adopted, it will be necessary to provide a credit programme enabling farmers to purchase the improved inputs, and a marketing structure that guarantees fixed and stable market prices throughout the year. KEYWORDS: Vigna unguiculata, cowpea, northern Nigeria, financial analysis, marketing